Factors affecting the character of plasma discharge with electrolytic cathode at a fixed pressure - Сергеева, Ольга Вячеславовна; Пивоваров, Александр Андреевич (Eastern-European Journal of Enterprise Technologies, 2015)
The influence of process parameters of plasma chemical treatment of aqueous solutions on the plasma discharge behavior at different values of the current, fixed pressure and the interelectrode gap was investigated in the paper. This was done to identify additional factors that affect the characteristics of the discharge - fluid system. As an electrolytic cathode, distilled and tap water, as well as CuSO4 and AgNO3 solutions in distilled water, were used. It was found that one of the factors affecting the gas-plasma discharge are charged bubbles in the electrolytic cathode layer, in the case when the metal electrode is put down in it. It was determined that bubbles could play a significant role in the delivery of charged particles to the gas-plasma discharge zone. In addition, microdischarges, emerging at a current I>125mA in gas bubbles are an additional source of charged particles. The results will be used to create a refined mathematical model of plasma chemical treatment of liquid media.